(3Cef GdeSJgdc GdEdcJQhfj s ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2008)
(3Cef GdeSJgdc GdEdcJQhfj,eaghe GdeSJgdc GdEdcJQhfj hhSGFd MeGjJg,eaghe GdeSJgdc GdGdcJQhfj,Gdeaghe GdYGe dMeGjI GdeSJgdc GdEdcJQhfj,Cef GdeSJgdc aj eQMdI EHQGe YbO GdESJgdGc,MeGjI QVGA GdeSJgdc aj eQMdI EHQGe YbO GdESJgdGc,GdEdJRGe bHd GdJYGbO HEYdGe GdeSJgdc GdGdcJQhfj,MeGjI GdeSJgdc aj ehGLgI GdGYdGfGJ GdEdcJQhfjI,Cef GdeSJgdc aj eQMdI JfajP GdYbO,GdGdJRGeGJ GdeJHGOdI Hjf WQaj YbO GdGSJgdGc GdGdcJQhfj,MeGjI GdeSJgdc aj ehGLgI GdYjhH GdNajI,OhQ GdgjFGJ aj MeGjI Cef GdeSJgdc GdGdcJQhfj,LgGR MeGjI GdeSJgdcs
(3HjHdjhZQGajG (B: (3U(B.195s
Keywords: (3GdeSJgdchfs; (3MeGjI GdeSJgdcs